UK guideline for the use of HIV Post-Exposure Prophylaxis Following Sexual Exposure, 2015. (August 2016) - Cresswell, Fiona; Waters, Laura; Briggs, Eleanor; Fox, Julie; Harbottle, Justin; Hawkins, David; Murchie, Martin; Radcliffe, Keith; Rafferty, Paul; Rodger, Alison; Fisher, Martin
We present the updated British Association for Sexual Health and HIV guidelines for HIV post-exposure prophylaxis following sexual exposure (PEPSE). This document includes a review of the current data to support the use of PEPSE, considers how to calculate the risks of infection after a potential exposure, and provides recommendations on when PEPSE should and should not be considered. We also review which medications to use for PEPSE, provide a checklist for initial assessment, and make recommendations for monitoring individuals receiving PEPSE. Special scenarios, cost-effectiveness of PEPSE, and issues relating to service provision are also discussed. Throughout the document, the place of PEPSE within the broader context of other HIV prevention strategies is considered.